A randomized unblinded trial to compare effects of intensive versus conventional lipid-lowering therapy in patients undergoing renal artery stenting. Issue 5 (November 2019) - Peng, Meng; Dong, Hui; Jiang, Xiongjing; Che, Wuqiang; Zou, Yubao; Zhang, Yuqing; Liu, Lisheng
Highlights: Intensive lipid lowering showed significant benefits in estimated glomerular filtration rate. Intensive lipid lowering offered more benefit in urinary albumin–creatinine ratio. The renal benefit of intensive lipid lowering was achieved without increased risk. Abstract: Background: Although current guidelines recommend the use of statins for severe atherosclerotic renal artery stenosis (ARAS), the renal protection of intensive lipid-lowering therapy in patients with ARAS who underwent stent placement remains uncertain. The aim of this study was to compare the renal-protective effect of intensive lipid lowering with that of conventional lipid lowering in patients with ARAS undergoing stent placement. Methods: A total 150 patients with severe ARAS undergoing stent placement were randomly (1:1) assigned to receive intensive lipid lowering [target low-density lipoprotein cholesterol (LDL-C) <70 mg/dL] or conventional lipid lowering (target LDL-C ≥70 mg/dL, <128 mg/dL). All patients received rosuvastatin. We adjusted LDL-C to the goal within two months after renal stenting and maintained stability. The primary endpoint was the change in estimated glomerular filtration rate (eGFR) at 12 months. Results: During the study period, LDL-C was lower in the patients with intensive lipid lowering than with conventional lipid lowering (at 12 months 58.0 ± 11.6 vs 85.1 ± 15.5 mg/dL, p < 0.001). At 12-month follow-up, eGFR (91.8 ± 30.2 vs 78.5 ± 19.5) mL/min·1.73 m 2, p = 0.002) and the increase in eGFR compared to baseline [14.8(IQR, 4.1, 26.7) vs −0.4(IQR, −9.5, 8.0) mL/min·1.73 m 2, p < 0.001] were higher in the patients with intensive lipid lowering than with conventional lipid lowering. Urinary albumin–creatinine ratio [42.2(IQR, 20.0, 60.9) vs 60.8(IQR, 26.8, 121.6) mg/g, p = 0.032] was lower and the decrease in urinary albumin–creatinine ratio compared to baseline [27.4(IQR, 3.0, 53.8) vs −3.1(IQR, −17.3, 30.9) mg/g, p = 0.001] was higher in the patients with intensive lipid lowering than with conventional lipid lowering. The restenosis rate (3.1% vs 3.4%, p = 0.711) and major clinical events (6.8% vs 11.0%, p = 0.37) were similar between the two groups. Conclusions: In patients with severe ARAS undergoing stent placement, intensive lipid lowering showed significant benefits in renal protection over conventional lipid-lowering therapy.